A new subspecies of giant sengi (Macroscelidea: Rhynchocyon) from coastal Kenya - Agwanda, Bernard R.; Rovero, Francesco; Lawson, Lucinda P.; Vernesi, Cristiano; Amin, Rajan (Zootaxa, 2021)
A new subspecies of giant sengi or elephant-shrew, first documented in 2008, is described from northern coastal Kenya. All five currently described species and most known subspecies of Rhynchocyon are compared to this new lineage. Molecular analyses using mitochondrial and nuclear markers from the single DNA sample available for the new lineage show differences from other forms and reveal a close relationship with the allopatric golden-rumped sengi R. chrysopygus (0.43% divergence at the 12S mitochondrial locus). This level of 12S divergence is similar to that between other subspecies pairs within Rhynchocyon. Based on three voucher specimens and 843 images from camera traps, the new lineage is similar to R. chrysopygus in the rufous-maroon sides and shoulders but is distinguished by the lack of the golden rump, the presence of jet-black distal rump and thighs, dark dorsal line, and a pronounced nuchal crest of hairs. Though it also shows superficial pelage similarities to two Tanzania species, R. udzungwensis and the dark coastal form of R. cirnei macrurus, the new form has differences in pelage coloration that are clearly diagnosable from all other taxa. This new lineage has an allopatric distribution to all known Rhynchocyon taxa, with the closest congener being R. chrysopygus located 140 km apart. We estimate a potential range size for the new taxon of ~1980 km2 in the Boni and Dodori National Reserves with habitat consisting of mixed thickets and dry forests. Because of its close genetic relationship with R. chrysopygus, its allopatric distribution, and divergent coloration, the new subspecies is designated Rhynchocyon chrysopygus mandelai. The previously described populations of R. chrysopygus from southern coastal Kenya are now designated R. chrysopygus chrysopygus. As the current severe political insecurity in the area threatens the new taxon, we hope that its description will help establish immediate conservation priorities and action for the subspecies and its habitat.